The Skill Gap in Software Industry: A Mapping Study - Diniz, Wellynton; Valença, Marcela; França, César; Santos, Alessandro; Pincovsky, Mariana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3351, 2024)
In recent decades, the growth potential of the software industry has raised concerns about the increasing number of unfilled positions due to a shortage of human capital, known as the "Skill Gap." This article presents findings from a Mapping Study (MS) conducted from September 2020 to February 2022, reviewing 8,622 articles, with 31 studies selected for analysis. The aim of this study was to map the causes, consequences, and mitigation strategies of the skill gap in software engineering. The main causes include the misalignment between academia and industry and rapid changes in market demand, resulting mainly in costs and missed opportunities. The article concludes by outlining potential avenues for future research in this domain.